Concomitant Presence of Aspergillus Species and Mycobacterium Species in the Respiratory Tract of Patients: Underestimated Co-occurrence? - Dellière, Sarah; Angebault, Cécile; Fihman, Vincent; Foulet, Françoise; Lepeule, Raphaël; Maitre, Bernard; Schlemmer, Frédéric; Botterel, Françoise (Frontiers in Microbiology, 2020)
Objectives: Aspergillus and Mycobacterium are opportunistic pathogens that can cause severe pulmonary diseases. To date, the clinical significance of their concomitant isolation and potential interactions in the lung remains poorly understood. The aim of this study was to assess the prevalence of their concomitant isolation from respiratory samples, and to depict the related clinical and microbiological characteristics. Methods: A retrospective monocentric study was conducted from January 2011 to December 2017, including all in-patients from whom positive cultures of Aspergillus and Mycobacterium were obtained on respiratory samples within a 3-month period. Clinical, radiological and laboratory data were analysed. Patients were categorised by a clinical and microbiological committee as “infected” or “colonized” by both pathogens according to current guidelines. Results: Overall, 140 patients had 1 respiratory samples positive for Mycobacterium and concomitantly sent for fungal culture, and 708 were positive for Aspergillus, concomitantly sent for mycobacterial culture. Only 50 had at least one positive culture for both Mycobacterium sp. and Aspergillus sp. Men represented 63% of patients, mean age was 61 years. A third of patients were immunocompromised and 92% had underlying lung diseases. Aspergillus was primarily found as a colonizing agent. Proportion of Mycobacterium Avium Complex (p=0.02) was higher in patients co-carrying Aspergillus spp. Conclusion: In this first study focusing on co-isolation of Mycobacteria and Aspergillus in patient’s respiratory samples, co-infection remains rare. Further studies are warranted in order to precise the exact relationship between these opportunistic pathogens and the clinical impact of co-isolations.